Implementation of Restorative Justice Policy for Children in Conflict with the Law (Case Study of the Women and Children Protection Unit at the Boyolali Police) - Virzha Reynata Putri; Tegar Harbriyana Putra; Adhiputro Pangarso Wicaksono (Penerbit Hellow Pustaka, 2025)
The development of criminal law in Indonesia has undergone a significant transformation, especially in handling cases involving children. Therefore, it is important to ensure that children in conflict with the law receive treatment in accordance with the principles of juvenile criminal justice, with a rehabilitative approach that focuses on recovery and social reintegration, not just punishment. This study aims to analyze how the restorative justice approach is applied in handling cases of children in conflict with the law, and to evaluate its ef ectiveness in creating restorative justice that can provide benefits for both perpetrators, victims, and the community. This study uses a juridical-empirical research type. Research data were obtained through interviews, observations and literature studies which were then analyzed using qualitative methods. Overall, the implementation of the restorative justice policy at the Boyolali Police deserves appreciation because it shows an implementation model that is in accordance with regulations. Although the potential for restorative justice is very large, its implementation is not always smooth and is often faced with obstacles that can hinder the achievement of a comprehensive sense of justice. In conclusion, although this policy has great potential in creating fairer and more rehabilitative justice for children, its implementation still requires optimal support through training, socialization, and cross-institutional coordination.